Degradation of β-N-methylamino-l-alanine (BMAA) by UV/peracetic acid system: Influencing factors, degradation mechanism and DBP formation. (November 2022) - Zhou, Shiqing; Huang, Jiamin; Bu, Lingjun; Li, Guangchao; Zhu, Shumin
Abstract: β- N -methylamino-l -alanine (BMAA) is a cyanobacterial neurotoxin associated with human neurodegenerative diseases, and its removal in drinking water is receiving increasing attention. In this study, the degradation of BMAA in UV/peracetic acid (UV/PAA) system was investigated. BMAA degradation followed the pseudo-first-order kinetic model. The synergistic effect of UV and PAA exhibited a great potential for BMAA degradation, which was attributed to the generation of a large number of reactive radicals, of which R–C was the most dominant contributor. We also explored the effects of different factors on BMAA degradation. The results showed that there was a positive correlation between BMAA degradation and PAA dosage, and the optimal effect was achieved at pH 7. Notably, the existence of water matrices such as bicarbonate (HCO3 －), chloride ion (Cl－), humic acid (HA) and algal intracellular organic matter (IOM) all inhibited the degradation of BMAA. Based on the identified intermediates, this study suggested that reactive radicals degraded BMAA mainly by attacking the carbon-nitrogen bonds on BMAA. Besides, comparing the effect of Cl－ on disinfection byproduct (DBP) formation in UV/PAA-post-PAA oxidation and UV/chlorine-post-chlorination systems, it was found that the former was more sensitive to the presence of Cl－. Graphical abstract: Image 1 Highlights: R–C. was the major contributor to BMAA degradation in UV/PAA system. BMAA degradation by UV/PAA system reached the optimal effect at pH 7. The existence of water matrices inhibited BMAA degradation in UV/PAA system. The destruction of carbon-nitrogen bond was the main process of BMAA degradation. UV/PAA-post-PAA oxidation system was sensitive to Cl－ in terms of DBP formation.